Communications - "Williams, Raymond" ("Middlesex, Eng", 1982)
Williams's fascinating investigation into forms of communication as they stood in 1962 - computers, radio, television, printing, photography, film - remains remarkably relevant today. The idea that reality is primary, and that communication of that reality secondary, is debunked - if we take the view that there is life, and then afterwards accounts of it, we degrade art and learning. Communications are, he argues, a major way in which reality is continually formed and changed. This is Williams's compelling introduction to modern means and institutions of communication.
Keywords: Communication